Behaviors of pregnant women regarding travel – the case of Türkiye - Erciyas, Şeyma Kilci; Cirban-Ekrem, Ebru; Demir, Rukiye; Aköz, Gizem (European Journal of Clinical and Experimental Medicine, 2024)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction and aim. With the development of transportation facilities and options, people can now travel easily. With women having a greater presence in the workforce, pregnant women can work until the eighth week before childbirth. This study was conducted to examine the behaviors of pregnant women regarding travel. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Material and methods. The data for this cross-sectional and descriptive study were collected from 519 pregnant women who voluntarily participated in the research and met the research criteria. The data were analyzed using the SPSS 24 software package. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Results. The average age of the participating pregnant women was 27.49±0.17, with 63.8% residing in urban areas, 74.8% be ing primiparous, and 47.6% being in the third trimester of pregnancy. A decrease in travel and car usage during pregnancy. The use of bus, train/tram/metro, taxi, bicycle/scooter, and motorcycle decreased during pregnancy, while use of car, plane, and ship/ferry increased. 81.9% of women always wore a seat belt during pregnancy. There was a statistically significant difference between the educational level of women and their car usage (p<0.005). It was found that women wore seat belts more frequently in the third trimester. As the number of pregnancies increased, the frequency of seat belt usage decreased. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusion. A decrease in the frequency of travel was observed among women during pregnancy. The levels of seat belt usage and correct seat belt fastening were unsatisfactory.